Photochemical decoration of silver nanoparticles on silver vanadate nanorods as an efficient SERS probe for ultrasensitive detection of chloramphenicol residue in real samples. (July 2021) - Barveen, Nazar Riswana; Wang, Tzyy-Jiann; Chang, Yu-Hsu
Abstract: Aquaculture and farming industries have been seriously threatened by the illegal use of antibiotics as feed-additives to benefit the animal growth. Although various conventional chemical sensing approaches have been widely explored for the trace-level detection of antibiotics, the effective and accurate monitoring techniques are still highly demanded. Herein, we propose a novel surface-enhanced Raman scattering (SERS) substrate with the heterogeneous integration of silver nanoparticles (Ag NPs) on silver vanadate nanorods (β-AgVO3 NRs) for the ultrasensitive detection of popular antibiotic, chloramphenicol (CAP). The photochemical decoration of Ag NPs on the surface of β-AgVO3 NRs remarkably enhances the Raman signal intensity of CAP molecules by the synergistic action of the mechanisms of electromagnetic and chemical enhancement. The structural features of Ag-NPs@β-AgVO3 -NRs favor the formation of hotspots at the interface between NPs and NRs by enhanced surface area and numerous active sites for the interaction with CAP molecules. The SERS measurement of CAP molecules on the Ag-NPs@β-AgVO3 -NRs shows a trace-level limit of detection (10 −10  M), high uniformity (5.29%), good reproducibility (3.89%), and high analytical enhancement factor (2.05 × 10 8 ). The proposed SERS substrate possesses excellent detection ability in monitoring real samples like tap water, milk and eye drops. Highlights: Novel photochemical decoration of silver nanoparticles (Ag NPs) on silver vanadate nanorods (AgVO3 NRs) has been demonstrated. The Ag-NPs@AgVO3 -NRs are used as the SERS substrate for the ultrasensitive detection of antibiotic, chloramphenicol (CAP). The Ag-NPs@AgVO3 NRs offers high analytical enhancement factor, excellent uniformity and reproducibility for the SPR sensing.